Parental smoking and young adult offspring psychosis, depression and anxiety disorders and substance use disorder - Sarala Marian; Mustonen Antti; Alakokkare Anni-Elina; Salom Carolinen; Miettunen Jouko; Niemelä Solja (OXFORD UNIV PRESS, 2022)
Background: To study the associations between maternal smoking during pregnancy and paternal smoking before pregnancy and adult offspring psychiatric disorders.
Methods: Prospective general population cohort study in Northern Finland, with people from the Northern Finland Birth Cohort 1986: 7259 subjects (77% of the original sample). Data on parental smoking were collected from parents during pregnancy using questionnaires. Outcomes were offspring's register-based diagnoses: any psychiatric disorder, any non-organic psychosis, mood disorder, anxiety disorder and substance use disorder (SUD) until the age of 29-30 years. Maternal smoking during pregnancy and paternal smoking before pregnancy were pooled to three-class variables: (i) none; (ii) 1-9 and (iii) ≥10 cigarettes/day. Information regarding both parents' alcohol use during pregnancy and at offspring age 15-16 years, maternal education level, family structure, parental psychiatric diagnoses and offspring gender, smoking, intoxication frequency and illicit substance use at the age of 15-16 years were investigated as covariates.
Results: In the multivariable analyses, maternal smoking during pregnancy did not associate with the studied outcomes after adjusting for offspring smoking and other substance use at offspring age 15-16 years and parental psychiatric disorders. However, paternal smoking ≥10 cigarettes/day before pregnancy [hazard ratio (HR) = 5.5, 95% confidence interval (CI) 2.7-11.2, P < 0.001] and paternal psychiatric disorders (HR = 1.7, 95% CI 1.1-2.8, P = 0.028) associated with offspring SUD after adjustments.
Conclusions: Information across the offspring life course is essential in exploring the association between parental smoking and offspring psychiatric disorders. Paternal smoking before pregnancy and paternal psychiatric disorders may act as modifiers in elevating the risk of substance-use-related problems among offspring.